THE EFFECT OF MADRASAH PRINCIPALS’ SPIRITUAL LEADERSHIP, WORK CULTURE, AND WORK DISCIPLINE ON TEACHER PERFORMANCE IN MADURANESE MADRASAH - Mohammad Irsyad Wira Saputra; Syunu Trihantoyo; Ainur Rifqi; Amrozi Khamidi; Alexis Arizabal Enriquez (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
This study examines the influence of the spiritual leadership of madrasah principals, work culture, and work discipline on teacher performance at State Senior High Schools (MAN) throughout Madura, East Java, Indonesia. Using an associative quantitative approach and an explanatory survey design, data were collected from 198 teachers selected through proportional random sampling from five MANs in the regencies of Bangkalan, Sampang, Pamekasan (MAN 1 and MAN 2), and Sumenep. The research instrument consisted of a 4-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression with tests for the prerequisites of normality, linearity, multicollinearity, and heteroscedasticity. The results of the study indicate that: (1) spiritual leadership has a positive and significant effect on teacher performance (β = 0.312; t = 4.21; p < 0.001); (2) work culture has a significant effect on teacher performance (β = 0.289; t = 3.87; p < 0.001); (3) work discipline has the largest partial effect (β = 0.341; t = 4.68; p < 0.001); and (4) all three variables simultaneously have a significant effect on teacher performance (R² = 0.614; F = 103.21; p < 0.001), explaining 61.4% of the variation in teacher performance. These findings support Spiritual Leadership Theory (Fry, 2003) in the sociocultural context of Islamic educational institutions and provide evidence-based recommendations for madrasah management. Keywords: Spiritual Leadership; Work Culture; Work Discipline; Teacher Performance; Madrasah Aliyah. Abstrak Penelitian ini mengkaji pengaruh kepemimpinan spiritual, budaya kerja, dan disiplin kerja kepala madrasah terhadap kinerja guru di Madrasah Aliyah Negeri (MAN) di seluruh wilayah Madura, Jawa Timur, Indonesia. Dengan menggunakan pendekatan asosiatif kuantitatif dan desain survei eksplanatori, data dikumpulkan dari 198 guru yang dipilih melalui pengambilan sampel acak proporsional dari lima lembaga MAN di Kabupaten Bangkalan, Sampang, Pamekasan (MAN 1 dan MAN 2), serta Sumenep. Penelitian ini menggunakan kuesioner skala Likert yang telah tervalidasi dan reliabel (skala 4 poin) yang mencakup empat variabel: kepemimpinan spiritual (10 item), budaya kerja (15 item), disiplin kerja (12 item), dan kinerja guru (10 item). Data dianalisis menggunakan regresi linier berganda dengan uji prasyarat termasuk normalitas, linearitas, multikolinearitas, dan heteroskedastisitas. Hasil penelitian menunjukkan bahwa: (1) kepemimpinan spiritual memiliki pengaruh positif yang signifikan terhadap kinerja guru (β = 0,312, t = 4,21, p < 0,001); (2) budaya kerja secara signifikan mempengaruhi kinerja guru (β = 0,289, t = 3,87, p < 0,001); (3) disiplin kerja memberikan pengaruh individu yang paling kuat (β = 0,341, t = 4,68, p < 0,001); dan (4) ketiga variabel tersebut secara bersama-sama dan signifikan memprediksi kinerja guru (R² = 0,614, F = 103,21, p < 0,001), menjelaskan 61,4% varians. Temuan ini memperkuat Teori Kepemimpinan Spiritual (Fry, 2003) dalam konteks sosiobudaya khusus lembaga pendidikan Islams. Kata Kunci: Kepemimpinan Spiritual; Budaya Kerja; Disiplin Kerja; Kinerja Guru; Madrasah Aliyah